2011
DOI: 10.1177/1948550611408118
|View full text |Cite
|
Sign up to set email alerts
|

Folk Beliefs About Human Genetic Variation Predict Discrete Versus Continuous Racial Categorization and Evaluative Bias

Abstract: What role do folk beliefs about human genetic variation play in racial categorization and evaluation? In two studies, the authors assessed or manipulated participants' estimates of the percentage of genetic material that human beings have in common and examined whether this variable would predict categorization (Study 1) and evaluation (Study 2) of faces that varied monotonically in Black-White racial composition. In both studies, participants with low (vs. high) genetic overlap beliefs implicitly perceived th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 44 publications
3
52
0
Order By: Relevance
“…Knowles & peng, 2005) or people rely on other cues, such as the stereotypicality of clothing (freeman, penner, Saperstein, Scheutz, & ambady, 2011) to help guide racial categorization. recent research has highlighted how a number of different social motivations can influence racial categorization of ambiguous and multiracial targets, including physical threat (Miller, Maner, & Becker, 2010), economic scarcity (Krosch & amodio, 2014;rodenheffer, hill, & lord, 2012), essentialism (chao, hong, & chiu, 2013;plaks, Malahy, Sedlins, & Shoda, 2012), and ideological motives (gaither, 2015;Krosch, Berntsen, amodio, Jost, & van Bavel, 2013;Kteily, cotterill, Sidanius, Sheehy-Skeffington, & Bergh, 2014). here, we expand on this prior research and examine the impact of two related social motives-belonging needs and racial identification-on the categorization of racially ambiguous targets.…”
Section: Categorization Of Racially Ambiguous Targetsmentioning
confidence: 99%
“…Knowles & peng, 2005) or people rely on other cues, such as the stereotypicality of clothing (freeman, penner, Saperstein, Scheutz, & ambady, 2011) to help guide racial categorization. recent research has highlighted how a number of different social motivations can influence racial categorization of ambiguous and multiracial targets, including physical threat (Miller, Maner, & Becker, 2010), economic scarcity (Krosch & amodio, 2014;rodenheffer, hill, & lord, 2012), essentialism (chao, hong, & chiu, 2013;plaks, Malahy, Sedlins, & Shoda, 2012), and ideological motives (gaither, 2015;Krosch, Berntsen, amodio, Jost, & van Bavel, 2013;Kteily, cotterill, Sidanius, Sheehy-Skeffington, & Bergh, 2014). here, we expand on this prior research and examine the impact of two related social motives-belonging needs and racial identification-on the categorization of racially ambiguous targets.…”
Section: Categorization Of Racially Ambiguous Targetsmentioning
confidence: 99%
“…Other experiments have found that manipulating racial bias leads to changes in essentialist thinking about race (Morton et al, ). Yet, unlike previous experiments (Andreychik & Gill, ; Chao et al, ; Kang et al, ; Kimel et al, ; Morton et al, ; Plaks et al, ), this study did not manipulate exposure to information about genetic variation or racial bias. Rather, it measured these variables.…”
Section: Mechanistic Limitations In the Present Experimentsmentioning
confidence: 88%
“…Prior experiments have shown that manipulating perceptions of genetic variation between racial or ethnic groups can cause changes in a variety of social‐psychological phenomena such as, racial bias (Andreychik & Gill, ; Kang et al, ; Plaks et al, ), inter‐ethnic hostility (Kimel, Huesmann, Kunst, & Halperin, ), and racial categorization (Chao et al, ). Other experiments have found that manipulating racial bias leads to changes in essentialist thinking about race (Morton et al, ).…”
Section: Mechanistic Limitations In the Present Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…People hold the ories about seemingly everything, including genetics (Plaks, Malahy, Sedlins, & Shoda, 2012), global warming (Dunlap, 1998), and obesity (McFerran & Mukhopadhyay, 2013). Some of these theories apply to people's own selves, including lay theories about willpower (Job, Walton, Bernecker, & Dweck, 2013;Miller et al, 2012), personality traits (Beer, 2002), and moods (Igou, 2004).…”
Section: Lay Theoriesmentioning
confidence: 99%